So f(m) = m+3 and f(m+1) = m(m+1)

Given, 8f(m + 1) – f(m) = 2

Or 8* (m+2)(m+1)- (m+3) = 2

8m^2 + 24m + 16 – m – 3 =2

8m^2 + 23m – 11 = 0

No integer solution so m is not odd means m is even.

Case 2) if m is even , m+1 = odd

So f(m+1) = m+3 and f(m) = m(m+1)

Given, 8f(m + 1) – f(m) = 2

Or 8(m+1 + 3) â€“ m(m+1) =2

8m + 32 â€“ m^2 â€“m =2

m^2 -7m -30 =0

(m+3)*(m-10)=0

M = 10 or -3

As m is even so m =10

**a)** 900+ Videos covering entire CAT syllabus**b)** 2 Live Classes (online) every week for doubt clarification**c)** Study Material & PDFs for practice and understanding**d)** 10 Mock Tests in the latest pattern**e)** Previous Year Questions solved on video